2008
DOI: 10.1021/ef8000345
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acidic Species in Athabasca Bitumen and Bitumen Heavy Vacuum Gas Oil by Negative-Ion ESI FT−ICR MS with and without Acid−Ion Exchange Resin Prefractionation

Abstract: Because acids in petroleum materials are known to corrode processing equipment, highly acidic oils are sold at a discount [on the basis of their total acid number (TAN)]. Here, we identify the acidic species in raw Canadian bitumen (Athabasca oil sands) and its distilled heavy vacuum gas oil (HVGO) as well as acid-only and acid-free fractions isolated by use of an ion-exchange resin (acid-IER) and negative-ion electrospray ionization Fourier transform ion cyclotron resonance (ESI FT-ICR MS) mass spectrometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 54 publications
5
81
0
3
Order By: Relevance
“…7 (9-12) and CN (18)(19)(20)(21)(22)(23) than those in E 1 and E 3 . In addition, few species with DBE < 4 were detected, suggesting that few saturated and unsaturated aliphatic amines exist in N 1 O 1 and N 1 O 2 classes.…”
Section: N 1 O 1 and N 1 O 2 Class Speciesmentioning
confidence: 88%
See 1 more Smart Citation
“…7 (9-12) and CN (18)(19)(20)(21)(22)(23) than those in E 1 and E 3 . In addition, few species with DBE < 4 were detected, suggesting that few saturated and unsaturated aliphatic amines exist in N 1 O 1 and N 1 O 2 classes.…”
Section: N 1 O 1 and N 1 O 2 Class Speciesmentioning
confidence: 88%
“…It has been successfully applied in molecular characterization of complex mixtures, such as petroleum products [21,22], shale oil [20], bio-oils [23][24][25] and coal derivates [26][27][28]. Meanwhile, electrospray ionization (ESI), a soft ionization technique, can selectively ionize polar molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The naphthenic acid purchased from Sigma-Aldrich is described as a technical grade extract from crude oil (no defined origin) with an acid number of 230 g/equivalent, which we use here as its molecular weight [29,30]. Recent studies have shown that naphthenates obtained from Alberta's oil sands have similar composition to those found in Sigma-Aldrich naphthenates, and are enriched in C 12 -C 16 fatty acid equivalents with 3-6 double bond equivalents [31].…”
Section: Chemicalsmentioning
confidence: 99%
“…Combined with soft ionization methods, e.g., electrospray ionization (ESI), FT-ICR MS was applied to investigate catalytic aquathermolysis of heavy oil (Wu et al 2005;Smith et al 2008;Colati et al 2013;Wang et al 2013). 10 mg oil sample was firstly dissolved in 1 mL toluene, and then diluted with toluene/ methanol (1:3, v/v) to yield a 0.2-mg/mL solution.…”
Section: Analysis Of Heavy Oil Samplesmentioning
confidence: 99%